(untitled) (Journal of Artificial Intelligence Research, 2023)
This research paper investigates the transformative role of deep learning in enhancing natural language processing (NLP) capabilities, particularly in multilingual systems. With globalization fostering communication across diverse languages, the necessity for sophisticated NLP tools has never been more critical. This study emphasizes how deep learning techniques, including recurrent neural networks (RNNs), convolutional neural networks (CNNs), and transformer models, are revolutionizing text understanding and translation processes. By employing large datasets and advanced algorithms, deep learning has significantly improved machine translation quality, sentiment analysis, and contextual understanding. Furthermore, this paper discusses the challenges faced in multilingual NLP, such as data scarcity for underrepresented languages and cultural nuances, and presents potential solutions leveraging deep learning methodologies. Through real-world applications and case studies, we showcase how these technologies facilitate effective communication in multilingual settings, thereby laying the groundwork for future innovations in NLP.